Evaluasi Implementasi Penanganan Dampak Sosial Ekonomi Akibat Pandemi Covid-19 - Aldrieva Audria Araminta Enoch; tarlani (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. In general, this study aims to evaluate the effectiveness of the implementation of socio-economic management due to the Covid-19 pandemic that has been carried out by the government. The impact of the Covid-19 pandemic which can simultaneously reduce the economy makes the government have to take the right and fast decisions. Indonesia was able to soften the Covid-19 pandemic through the PEN program which has become the center of attention of several countries, such as America. Bandung is the city with the highest population density on the island of Java and the performance of the Bandung city government is ranked first in accelerating the handling of Covid-19. The research method uses qualitative research methods. The data analysis used by the researcher is Comparative Analysis and LFA (Logical Framework Analysis). Evaluation of the results of the implementation of the handling of social impacts in the City of Bandung shows that the handling carried out by the government has not been optimal in dealing with problems caused by the Covid-19 pandemic. This is due to government decision-making that hampers economic growth, limited use of technology, and limited health services. Abstrak. Secara umum, penelitian ini bertujuan untuk mengevaluasi sejauh mana efektivitas pelaksanaan penanganan sosial ekonomi akibat pandemi Covid-19 yang telah dilakukan pemerintah. Dampak pandemi Covid-19 yang mampu menurunkan perekonomian secara serentak membuat pemerintah harus mengambil keputusan yang tepat dan cepat. Indonesia mampu melunakan pandemi Covid-19 melalui program PEN menjadi pusat perhatian beberapa negara, seperti Amerika. Kota bandung merupakan kota dengan kepadatan penduduk tertinggi di pulau jawa dan kinerja pemerintah kota bandung menduduki peringkat pertama dalam percepatan penanganan Covid-19. Metode penelitian menggunakan metode penelitian kualitatif. Analisis data yang digunakan oleh peneliti adalah Analisis Komparatif dan LFA (Logical Framefork Analysis). Evaluasi terhadap hasil capaian dari implementasi penanganan dampak sosial Kota Bandung menunjukkan bahwa penanganan yang dilakukan pemerintah belum optimal dalam menangani permasalahan yang diakibatkan pandemi Covid-19. Hal tersebut dikarenakan pengambilan keputusan pemintah yang menghambat pertumbuhan ekonomi, adanya keterbatasan pemanfaatan teknologi, dan layanan kesehatan yang terbatas.